Third degree heart block and elevated troponin following acute respiratory hypoxic failure in a COVID-19 recovered patient in the absence of coronary artery disease. Issue 2 (2021) - , Samer Khalil, Andrew Collins; Mubarak, Naser; Khali, Taher
No abstract available